Frans Masereel - Zweig, Stefan; Vorms, Pierre; Pommeranz-Liedtke, Gerhard; Von der Gabelentz, Hanss-Conon (Dresden : Verlag der Kunst, 1961)
Bibliotheek Jan Baghus
Duits
Monografie
Keywords: Masereel, Frans; kunst